Clinico-epidemiological characteristics of patients reported with intra-hospital infection in the Pediatric Intensive Care Unit. Cienfuegos, 2015-2019 - Lourdes Elena Duany Badell; Sadis Suárez del Villar Seuret; Tania Cantero Martínez; Maribel Caridad Águila Toledo; Sarah Hernández Malpica; Vivian Hernández Monsón (Medisur)
Background: the rate of intra-hospital infections is one of the qualities of services’ indicators; It acquires greater importance in pediatric intensive care units, due to its high incidence and severity. Objective: to characterize the cases of infection associated with health care in the Pediatric Intensive Care Unit. Methods: retrospective descriptive study of patients admitted to the Pediatric Intensive Care Unit at the Paquito González Cueto University Pediatric Hospital, Cienfuegos, who acquired an infection in this unit, in the period from 2015 to 2019. The analyzed variables were: age at discharge, sex, location of sepsis, high-risk procedure, use of microbiological support and its positivity, lethality. Results: the average rate of infection associated with care was 3.5 per 100 discharges; Children under one year of age were more affected with 27.3%. Respiratory infection predominated with 46.8%. The use of venous catheterization occurred in 94.8% of the cases and antimicrobials due to previous infections were applied in 49.4%. Microbiological support was performed in 77.9% and it was positive in 76.7%. Gram negative germs predominated. Four patients died. Conclusions: the nosocomial infection rate is comparable with the numbers reported internationally. Children under one year of age are more infected, with a non-negligible lethality, so prevention and control measures aimed at the main risk factors for their appearance must be taken to extremes.